Outcome of selective ramisectomy for botulinum toxin resistant torticollis. Issue 4 (1st October 1998) - Ford, Blair; Louis, Elan D; Greene, Paul; Fahn, Stanley
Abstract : OBJECTIVE: To investigate the long term outcome of selective ramisectomy denervation in patients with botulinum toxin resistant spasmodic torticollis. BACKGROUND: The published surgical series of ramisectomy treatment for torticollis do not provide systematic information on patients who develop resistance to the current standard of treatment—botulium toxin injections. Moreover, there is little information on surgical outcome using rating scale measurements of torticollis, or assessments of functional and occupational capacity. METHODS: Using a structured interview format and videotape assessments of severity of dystonia in a retrospective fashion, detailed follow up information was obtained on 16 patients who underwent open label selective denervation for severe, disabling torticollis, refractory to injections of botulinum toxin. RESULTS: Of 16 patients with disabling torticollis followed up postoperatively for a mean of 5 years, six (37.5%) had a moderate or complete return of normal neck function, as determined using functional capacity scales, whereas 10 had only minimal relief of dystonia or gain in function. Six of the 16 patients (37.5%) underwent a second peripheral denervation operation, and one required a third. Of 11 patients working outside the home before surgery, nine were disabled by dystonia, and only one continued to work after surgery. Dystonia rating scale scores of videotaped examinations using a modification of the Toronto Western Spasmodic Torticollis Rating Scale (TWSTRS) improved in 12 of 14 patients (85.7%) who underwent selective ramisectomy. When patients with primary botulinum toxin resistance were excluded, the magnitude of benefit for this subgroup was 31.9% of the baseline dystonia score (p<0.0002), comparable with the degree of improvement in a group of control patients receiving botulinum toxin treatment for torticollis. CONCLUSION: About one third of patients with torticollis resistant to injections of botulinum toxin may derive modest long term functional improvement from selective denervation, with a reduction in dystonia by about 30%, but remain unable to work.